Validation of the Chinese names Bischofia racemosa (Euphorbiaceae), Ulmus erythrocarpa and Ulmus multinervis (Ulmaceae) - Duan, Yi-Fan; Li, Yong-Fu; Yang, Xin-Xin; Wang, Xian-Rong (Phytotaxa, 2016)
While studying the type specimens housed at NF (Nanjing Forestry University Herbarium, Nanjing, China), we found that three names, Bischofia racemosa Cheng & Chu in Cheng et al. (1963: 13) (Euphorbiaceae), Ulmus erythrocarpa Cheng (1958: 72) (Ulmaceae) and U. multinervis Cheng (1958: 70) (Ulmaceae), were not validly published, because two or three gatherings were designated as types for each name (ICN Art. 40.2; McNeill et al. 2012). Here we validate these three names by choosing one specimen as the type for each of them.